Lung volumes and spirometry (Henry Stewart Talks, 2025)
Importance of lung volumes, Definitions of lung volumes, Spirometry assessment and key parameters, Interpretation of spirometry patterns, Clinical use of spirometry in asthma and COPD, Advanced lung volume measurement techniques, Advanced lung volume relevance in complex cases